Artificial cognition systems - Loula, Angelo 1977-.; Gudwin, Ricardo 1967-.; Queiroz, Joao 1963-.; Gale Group (Hershey, Penn. Idea Group Pub., 2007)
"This book presents recent research efforts in Artificial Intelligence about building artificial systems capable of performing cognitive tasks. A fundamental issue addressed in this book is if these cognitive processes can have any meaningfulness to the artificial system being built"--Provided by publisher.
The goose, the fly, and the submarine navigator : interdisciplinarity in artificial cognition research / Alexander Riegler -- An embodied logical model for cognition in artificial cognition systems / Guilherme Bittencourt, Jerusa Marchi -- Modeling field theory of higher cognitive functions / Leonid Perlovsky -- Reconstructing human intelligence within computational sciences : an introductory essay / Gerd Doeben-Henisch -- Stratified constraint satisfaction networks in synergetic multi-agent simulations of language evolution / Alexander Mehler -- Language evolution and robotics : issues on symbol grounding and language acquisition / Paul Vogt -- Evolutionary robotics as a tool to investigate spatial cognition in artificial and natural systems / Michela Ponticorvo, Richard Walker, Orazio Miglino -- The meaningful body : on the differences between artificial and organic creatures / Willem Haselager, Maria Eunice Q. Gonzalez -- Making meaning in computers : synthetic ethology revisited / Bruce MacLennan -- Environmental variability and the emergence of meaning : simulational studies across imitation, genetic algorithms, and neural nets / Patrick Grim, Trina Kokalis -- Mimetic minds : meaning formation through epistemic mediators and external representations / Lorenzo Magnani -- First steps in experimental phenomenology / Roberto Poli.
Electronic reproduction.
Keywords: Artificial intelligence -- Research; Cognitive science -- Research; Electronic books